The Influence of Student Income and Lifestyle on Paylater Services (Case Study on Students of The Economics Education Study Program, HKBP Nommensen University, Pematangsiantar) - Antika, Rindi; Gultom, Binsar Tison; Sitorus, Debbi Petra Meyana (CV Putra Publisher, 2025)
This study aims to determine the effect of income and lifestyle on Paylater services among students of the Economics Education Study Program at HKBP Nommensen University, Pematangsiantar. This research employs a quantitative approach with an associative research design. The population consisted of 305 active students, and a sample of 173 respondents was selected using the purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression tests with the assistance of SPSS version 25. The results of the study indicate that (1) income has a positive and significant effect on Paylater services, (2) lifestyle has a positive and significant effect on Paylater services, and (3) income and lifestyle simultaneously have a significant influence on Paylater services among students. This implies that the higher the income and the more consumptive the lifestyle of students, the greater their tendency to use Paylater services